Occlusion of a left superior vena cava-coronary sinus connection in a child with Glenn dysfunction by the transcatheter approach - Murat Saygi; Hasan Tahsin Tola; Alper Guzeltas; Ender Odemis (Türk Kardiyoloji Derneği Arşivi, 2014)
A 14-year-old male patient presented with cyanosis and tiredness. The patient had undergone a Glenn procedure at age 12 following the echocardiographic determination of a double inlet left ventricle, ventriculoarterial discordance, moderate valvular–subvalvular pulmonary artery stenosis, non-restrictive inlet ventricular septal defect and right ventricle hypoplasia; his oxygen saturation was 70%. Echocardiography evaluation showed retrograde flow from the vena cava superior to the innominate vein and an left superior vena cava opening into the coronary sinus. Here, we report the case of a patient evaluated for Glenn dysfunction in whom an increase in oxygen saturation was observed following transcatheter occlusion of the left superior vena cava–coronary sinus connection using an Amplatzer® septal occluder.